PENGAWASAN TERHADAP LABEL MAKANAN KEMASAN DI KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Ade Pratiwi Susanty (Ensiklopedia of Journal, 2019)
The guidance and supervision of the Pekanbaru City Government on the label of packaged food products, especially home industry products, turned out to not work optimally. Although the government has conducted socialization, the socialization carried out has not been optimal. This is evidenced that there are still many business people who do not understand the label. In addition, supervision carried out by the government is also ineffective because there are still many packaged food products circulating that do not yet have a label that complies with the provisions of applicable legal regulations. The implementation of the regulation of labeling packaged food products as regulated in Law Number 18 of 2012 concerning Food and Government Regulation Number 69 of 1999 concerning Labels and Food Advertising in the City of Pekanbaru is still not running optimally. This is evidenced by the fact that there are still many business people who are not aware of the regulations governing labels on packaged food products, so that the implementation of the labeling regulations for food products has not been effective.